Effects of heating followed by water quenching on strength and microstructure of ultra-high performance concrete - Li, Ye (2021)
This paper presents an experimental study on the effects of elevated temperature and water quenching on compressive strength and microstructure of ultra-high performance concrete (UHPC) containing polypropylene (PP) fiber, steel fiber, and larger aggregates. UHPC samples were exposed to elevated temperature up to 900 °C. The residual strengths of the samples were measured after furnace cooling or immediate quenching in water. Microstructures and phase change of UHPCs were investigated by using X-ray Diffraction (XRD) and Field Emission Scanning Electron Microscope (FESEM). Test results show that the compressive strength increased significantly after exposure to 300 °C due to further hydration of unhydrated cement clinkers but start to decrease sharply after 600 °C exposure due to decomposition of hydration products. Steel fiber had beneficial effect, but PP fiber and larger aggregate reduced the compressive strength of UHPC because they promoted damage at micro scale. Water quenching decreased compressive strength significantly for all exposure temperatures. This reduction is mainly attributed to the formation of microcracks caused by high thermal stress.